2013
DOI: 10.2196/resprot.2897
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Compliance, Acceptance, and Usability of a Web-Based eHealth Intervention for Parents of Children With Infantile Hemangiomas: Usability Study

Abstract: BackgroundInfantile hemangiomas (IH) are common benign vascular tumors in children. Recognition and timely referral of high risk IH to specialized centers is important. This might be achieved by involving parents in the care for IH by means of an eHealth intervention.ObjectiveThe objective of our study was to evaluate parent compliance, acceptance, and usability of an open access, Web-based eHealth intervention (including e-learning and e-consult) designed to increase parents’ knowledge and (risk) evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
3
18
0
1
Order By: Relevance
“…[231][232][233][234]239,248 The majority of studies were conducted in the USA (17 studies 230,231,234,236,[238][239][240][241][242][243][244]246,248,255 ); other main locations were Australia (three studies 227,228,235 ), the Netherlands (three studies 245,247,249 ), Sweden (three studies 233,237,250 ) and the UK (two studies 232,256 ).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[231][232][233][234]239,248 The majority of studies were conducted in the USA (17 studies 230,231,234,236,[238][239][240][241][242][243][244]246,248,255 ); other main locations were Australia (three studies 227,228,235 ), the Netherlands (three studies 245,247,249 ), Sweden (three studies 233,237,250 ) and the UK (two studies 232,256 ).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, as authors may have described similar technologies using different names, there may be some overlap between categories. Videoconferencing or video consultation was the most frequently used tool (14 studies 227,228,233,235,236,238,[240][241][242][243][244]246,248,253 ), followed by e-mails or web messaging systems (13 studies 223,[229][230][231][232]234,[237][238][239]245,247,249,250,254,256 ). Other categories were web chat (two studies 239,255 ) and SMSs (one study 224 ).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Berk et al (2013) reported comparatively higher levels of agreement regarding the usefulness of a website containing guidelines for caregivers of adults with bipolar disorder. Likewise, a study on the acceptance of a web-based e-health intervention for parents of children with infantile hemangiomas showed higher agreement rates (de Graaf et al 2013). It is assumed, that the higher acceptance was due to the fact that the respective website was aimed at one target group (caregivers) and one narrowly defined topic (bipolar disorders, infantile hemangiomas).…”
Section: Discussionmentioning
confidence: 99%